Analisis Motivasi dan Lingkungan Keluarga terhadap Minat Melanjutkan Studi ke Perguruan Tinggi Siswa Berprestasi Kelas XI Teknik Pemesinan SMK Negeri 1 Padang - Devidto Kurnia Putra; Irzal Irzal; Febri Prasetya (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Interest is a feeling of preference and attraction toward something or an activity without being told, typically marked by enjoyment or attention focused on a particular object of interest. This study aims to determine the influence of motivation and family environment on the interest in pursuing higher education among high-achieving 11th-grade students in the Mechanical Engineering program at SMK Negeri 1 Padang. This research is a descriptive quantitative study using multiple linear regression methods. The population consisted of 30 high-achieving students ranked 1–15 from each class (XI TP A and XI TP B) at SMK Negeri 1 Padang. The entire population was used as the sample using the census method (saturated sampling). Data collection instruments included questionnaires using a Likert scale, which had been tested for validity and reliability. The study was conducted at SMK Negeri 1 Padang, with the research subjects being 11th-grade students in the even semester of the 2024/2025 academic year. The instrument used in this research was a questionnaire. Based on the research findings and data analysis, it can be concluded that motivation and family environment have a significant influence, both partially and simultaneously, on students’ interest in continuing their studies to higher education. The average score for motivation falls into the high category (72.86), the average for the family environment is in the moderate category (44.73), and the average for interest is in the high category (73.86). Together, the variables of motivation and family environment can explain a substantial portion of the variation in students’ interest in pursuing higher education.